Evaluation of minicircle-induced pluripotent stem cell - Daneshvar, Nasibeh (2014)
Due to the risk of insertional mutagenesis, viral transduction has been increasingly replaced by non-viral methods to generate iPSCs. One technique that has not yet been explored enough is the use of “minicircle” DNA. The pMC.LGNSO plasmid is known as the parental DNA structure and is utilized to generate minicircle vectors which are episomal DNA vectors that are created as circular expression cassettes without any backbone of bacterial plasmid DNA. Their smaller molecular size gives them this ability to have more efficient transfections alongside sustained expression last for weeks in comparison to standard plasmid vectors which extremely work only for a week. Minicircle DNA also benefits from higher transfection efficiencies and longer ectopic expression. The Transfection efficiency of the minicircle vectors can be monitor during the plasmid transfections by EGFP expression under a fluorescence microscope. This minicircle-based induction of pluripotency method is beneficial for obtaining transgene-free hiPSCs from human donors which are clinically applicable cell sources. Such techniques have the characteristic of developing patient or disease-specific cell lines to develop further translational and disease modeling researches. Here, we report the use of a single minicircle vector to generate transgene-free iPS cells from adult human mesenchymal stem cells. 50,000 cells/well was considered as the best amount of seeded cells to achieve the highest amount of transfection. Moreover, the results highlighted the utilization of antibiotics to avoid cell contamination. This experience also demonstrated that the 1:2 (3μg DNA/6 μL LTX) ratio and 150 μl of DNA/LTX complex in presence of medium at the transfection time will produce the highest level of genes expression. The human MSCs were transfected twice using minicircle DNA/Lipofectamine LTX complex. The GFP-positive cells were observed by florescent microscopy 24 h posttransfection. Human ESC-like colonies with a tightly packed, domelike structure began to appear 7 to 10 days after second transfection. The pluripotency of the derived iPSC lines was verified by qRT-PCR and immunochemical staining (ICC) techniques to possess pluripotent markers and cause embryoid body (EB) differentiation. Based on the results of RT-PCR, the expression of three embryonic germ layers markers showed that the EBs are successfully differentiated. Thus the iPSCs were shown to possess of the pluripotency of ESC thus has potential for use in cell-based treatment in human medicine. The developed method of iPSC producing in this study is measured as a fast and inexpensive technique, which benefits from using a non-viral vector to develop human iPSCs safely. This method also utilizes feeder-free cell culture technique to remove concerns of possible contaminations that could occur in the process of utilizing of mouse embryonic fibroblast feeder layers. This method can have a huge effect on making use of MSCs which are easily obtainable from clinical wastes discarded after child delivery.